Eco-friendly manufacturing towards the industry of the future with a focus on less cutting fluid and high workpiece quality applied to the grinding process - Sato, Bruno Kenta [UNESP]; Lopes, José Claudio [UNESP]; Rodriguez, Rafael Lemes [UNESP]; Garcia, Mateus Vinicius [UNESP]; Ribeiro, Fernando Sabino Fonteque [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2021)
The global effort in order to reduce impacts to the environment and people produces the need for new technologies as an eco-friendly alternative to replace the cutting fluids, which directly affects the grinding process. In this sense, grinding uses a large amount of cutting fluid to mitigate high temperatures and their consequences. Thus, alternatives to the cutting fluid should reduce the use of fluid combined with the maintenance of production, like minimum quantity lubricant (MQL). The MQL with pure oil tends to produce results close to the cutting fluid method, but improvements in its cooling capacity are still mainly needed. Therefore, this work studies the MQL with oil-water dilution (1:1, 1:3, and 1:5) varying the feed rate in the external cylindrical grinding of AISI 4340 steel, comparing it with pure MQL and the conventional method with abundant cutting fluid. The results of applying MQL 1:5 produced workpieces with similar quality to that obtained with the conventional cutting fluid. In addition, the MQL method resulted in less variation with the increase of feed rate when compared to other lubri-refrigerant methods applied.
Keywords: Addition of water; AISI 4340; Feed rate; Grinding; MQL